2002
DOI: 10.1093/ortho/29.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Perception of orthodontic treatment need: opinion comparisons of orthodontists, pediatric dentists, and general practitioners

Abstract: Orthodontists, general dental practitioners, and pediatric dentists in this sample exhibit high levels of agreement on orthodontic treatment need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
1
17
2
Order By: Relevance
“…[8][9][10][11][12] To investigate the patients' temperamental dispositions, understood as inherited personality traits, the EAS-C Temperament Questionnaire, version for children assessed by their parents, was used. 13 The A. H. Buss and R. Plomin EAS Temperament Survey provided the theoretical basis for the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] To investigate the patients' temperamental dispositions, understood as inherited personality traits, the EAS-C Temperament Questionnaire, version for children assessed by their parents, was used. 13 The A. H. Buss and R. Plomin EAS Temperament Survey provided the theoretical basis for the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature, it was assumed that the formal features of the child's temperament may be decisive when it comes to adopting a new pro-health attitude. [8][9][10][11][12] It was also assumed that the effectiveness of motivating a child to systematically wear a removable appliance may depend on the caregivers' dispositions such as a strong sense of self-efficiency, personality dispositions and parental attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…T he dental profession is unique among the various types of health care providers in that, in most instances, the dental practitioner alone is responsible for performing a diagnosis, determining treatment options, and performing the chosen treatment. Variations have been found among dental practitioners regarding diagnosis and treatment of dental caries lesions, 1-5 periapical lesions, [6][7][8][9][10][11][12][13] third molars, [14][15][16][17] and malocclusions, 18,19 as well as differences in antibiotic prescription habits after endodontic treatment 20 and extractions. 21 This variation can be explained by differences in culture, patient preferences, treatment methods, prevalence of disease, practitioner to patient ratio, available resources, reimbursement systems, postgraduation education, and the existence and application of clinical guidelines.…”
mentioning
confidence: 99%
“…General dentists refer the patients to orthodontist, and therefore their perception of malocclusion are also vital. Studies evaluating treatment outcome by general dentists, compared with orthodontists (16,17) have been published. Shaw and Prahl-Andersen showed that orthodontists think more critically than society in general (1,14).…”
Section: Resultsmentioning
confidence: 99%